2022
DOI: 10.1039/d1fo03759e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of n-6 PUFA-rich soybean oil, MUFA-rich olive oil and camellia seed oil on weight and cardiometabolic profiles among Chinese women: a 3-month double-blind randomized controlled-feeding trial

Abstract: Previous studies have suggested that replacing saturated fat by unsaturated fats are beneficial for cardiometabolic health. However, research that directly compare the effects of polyunsaturated fatty acids (PUFAs) and monounsaturated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The potential cardioprotective benefits of OO consumption have been demonstrated in several studies and are summarized in Table 2 [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential cardioprotective benefits of OO consumption have been demonstrated in several studies and are summarized in Table 2 [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…The previously mentioned studies have experimented the benefits of OO on health, nevertheless, it is also important to compare the effects of MUFA, in the form of OO, and PUFA. Wu et al (2022) explored this difference among middle-aged and elderly Chinese women at high cardiovascular risk, in a 3-month, randomized, controlled-feeding trial [85]. Ninety participants were randomized into 3 groups: diets using n-6 PUFA-rich soybean oil, MUFA-rich OO, and MUFA-rich camellia seed oil as cooking oils and as part of the traditional Chinese eating habits, consuming only the food given for lunch and dinner while refraining from taking edible oils for breakfast.…”
Section: Olive Oil Effects On Cardiovascular Diseases (Cvd)mentioning
confidence: 99%
“…To the best of our knowledge, this is the first study suggesting an interaction between SIDT2 and nutrients with HDL-c concentrations. However, current studies have also observed significant interactions between the genetic variants involved in HDL-c metabolism and nutritional factors on HDL-c levels [ 64 , 65 , 66 , 67 ]. Supporting our results, earlier studies have shown that a high-fat intake can increase the HDL-c concentrations through more substrate provided in the chylomicron-derived triglycerides and increased lipoprotein lipase (LPL) activity.…”
Section: Discussionmentioning
confidence: 99%
“…A previous investigation demonstrated that serum HDL-c concentrations are low in people consuming high saturated fatty acids (SFAs) and are unaffected by the intake of either MUFAs or PUFAs [ 69 ]. However, an early controlled-feeding trial study suggested that older women who consume higher amounts of dietary MUFAs have a more favorable effect on metabolic profiles, including HDL-c levels, compared to those who consume a diet rich in PUFAs [ 65 ]. In addition, observational studies have also explored the interaction between dietary factors on dyslipidemias.…”
Section: Discussionmentioning
confidence: 99%
“…Camellia oil contains a variety of active substances, which have the functions of strengthening heart and lowering cholesterol, and can prevent a variety of cardiovascular and cerebrovascular diseases caused by arteriosclerosis. erefore, it is called "Changshou oil," and it is a healthy high-grade edible oil promoted by FAO [1]. Camellia oil cultivation has the advantage of not occupying cultivated land, so developing camellia oil industry has become an important deployment of edible oil safety strategy [2].…”
Section: Introductionmentioning
confidence: 99%